BLACK CUMIN (NIGELLA SATIVA) EFFECT ON BLOOD PRESSURE, MEAN ARTERIAL PRESSURE, PROTEINURIA IN PREECLAMPTIC MODEL RATS - MARPAUNG, JOHNY; SIREGAR, M. F. G.; SITEPU, MAKMUR; BACHTIAR, ADANG (International Journal of Current Pharmaceutical Research, 2020)
Objective: This research aimed to show effect of black cumin (nigella sativa) on blood pressure, mean arterial pressure (MAP), proteinuria in preeclamptic model rats. Methods: This is analytical research with true experimental design in laboratory pregnant female rats (Rattus norvegicus), which get black cumin seed extract (Nigella sativa) at a dose of 500 mg/kg/day and 2000 mg/kg/day. Treatment of all samples was performed simultaneously and during the treatment was observed using Postest Only Control Group Design. The research was conducted at Biology Laboratory in July 2019. To assess the comparison of parameters (systolic and diastolic blood pressure, mean arterial pressure and proteinuria) between groups the ANOVA test was used if the data were normally distributed and Kruskal Wallis test was used if the data were abnormally distributed. Results: Systolic and diastolic blood pressure and MAP decreased in preeclampsia models rats by administering 500 mg (P1) and 2000 mg (cumin) black cumin extract (P2). However, a dose of 2000 mg black cumin extract had a more significant decrease in systolic blood pressure and MAP. The results of this research indicate that all treatment groups showed improvement after day 9 of the administration of nigella that no treatment group showed proteinuria. Conclusion: Black cumin is proven to reduce systolic and diastolic blood pressure, Mean Arterial Pressure and proteinuria.